The Hero’s Journey Of Encounter With The Transcendental In Paulo Coelho’s The Alchemist (1988) - Enteghar Kahina; Rahil Faiza (University of Eloued جامعة الوادي, 2025)
This study examines the journey of spiritual enlightenment in Paulo Coelho’s The Alchemist (1988). It shows that the dessert space sustains Santiago by illuminating mystical experiences which increase his awareness of the world beyond the phenomenal one. The paper argues that the boy’s journey bears strong affinities to Joseph Campbell’s description of the heroic journey and ends up with the hero finding a distinctive treasure which lies in spiritual wakefulness and encounter with the Divine. The reading of The Alchemist shows that the belief in the desert as a space of rejuvenation and devotion did not end with the Desert Fathers as it still intrigues postmodern authors. The novel redeems the world of the senses by believing that it holds a spark of the Ideal one.
Ex Professo. Vol. 10. N1
Keywords: Paulo Coelho; the Alchemist; desert; Joseph Campbell; mysticism.; The Alchemist; Joseph Cambell; mysticism